2020
DOI: 10.1590/0034-7167-2019-0162
|View full text |Cite
|
Sign up to set email alerts
|

Predicting dimensions of clinical-functional conditions and cognition in the elderly

Abstract: Objective: To evaluate the predictive dimensions of clinical-functional conditions and the cognitive capacity of elderly people living at home. Method: Cross-sectional, population-based, analytical, quantitative study was utilized. For data collection, an instrument with sociodemographic and behavioral variables, the Functional Clinical Vulnerability Index; and, to assess cognition, the Mini-Mental State Examination (MMSE) was used. Descriptive analyzes and statistical tests were conducted. Results: 305 elde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 17 publications
(23 reference statements)
0
3
0
11
Order By: Relevance
“…7 Another study of 394 older adults found that 19.5% were at high risk, 28% at moderate risk, and 52.5% at low risk. 8 Silva et al 9 found that 71.8% of their sample of older adults were at low risk, 22% at moderate risk and 6.2% at high risk.…”
Section: Discussionmentioning
confidence: 97%
“…7 Another study of 394 older adults found that 19.5% were at high risk, 28% at moderate risk, and 52.5% at low risk. 8 Silva et al 9 found that 71.8% of their sample of older adults were at low risk, 22% at moderate risk and 6.2% at high risk.…”
Section: Discussionmentioning
confidence: 97%
“…Cabe ressaltar que a literatura aponta que idosos com melhor índice de autopercepção da saúde têm menores riscos de mortalidade (Ribeiro et al, 2018). No Rio Grande do Sul, o estudo realizado com 305 idosos apresentou resultados positivos quanto à autopercepção da saúde, onde cerca de 51,8% a consideravam excelente, boa ou muito boa (Silva et al, 2020).…”
Section: Discussionunclassified
“…Research, Society andDevelopment, v. 11, n. 2, e32911224351, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i2.24351 No atual estudo houve uma prevalência positiva significativa na cognição das idosas estudadas com percentual mínimo de 75,8% em uma das perguntas que são realizadas nesse domínio do instrumento. Comparado a um estudo realizado por Silva et al (2020) em domicílio com 304 idosos do Rio Grande do Sul, percebeu-se que 75,1% não apresentavam nenhum declínio na cognição.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Os dados do presente estudo apontam que o desempenho cognitivo subjetivo é bastante afetado na população idosa. Dentre os idosos estudados, um terço apresentou alguma queixa cognitiva, achado semelhante aos encontrados em outros estudos que relataram comprometimento cognitivo em 28,14% e 37,8% dos idosos 13,14 . Índices mais baixos, entretanto, foram encontrados em trabalhos publicados por Silva 13 , 24,9%, Gurian 15 , 18,3%, e Jacobs 14 , 25,6%.…”
Section: Discussionunclassified